The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym12030619
|View full text |Cite
|
Sign up to set email alerts
|

A Unidirectional Soft Dielectric Elastomer Actuator Enabled by Built-In Honeycomb Metastructures

Abstract: Dielectric elastomer actuators (DEAs) are able to undergo large deformation in response to external electric stimuli and have been widely used to drive soft robotic systems, due to their advantageous attributes comparable to biological muscles. However, due to their isotropic material properties, it has been challenging to generate programmable actuation, e.g., along a predefined direction. In this paper, we provide an innovative solution to this problem by harnessing honeycomb metastructures to program the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The theoretical model predicts that the use of a negative Poisson’s ratio structures in linear actuator systems would lead to optimized work in a high-stroke, low-force configuration . Several studies have shown that materials with a negative Poisson’s ratio can exhibit shape memory behavior, which could be used for building thermally activated medical stents and soft actuators. ,, A honeycomb structure has been as well used for DEA preparation, where the use of this structure gives additional prestretching of the DE membrane and allows a high anisotropy that leads to uniaxial actuations . The concept of folding and unfolding of cells using a pneumatic actuation has been described as well by Overvelde et al A prepared actuator showed a high degree of freedom, being able to actuate in various dimensions and being able to be folded flat .…”
Section: Mechanisms Of Shape Transformation and Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical model predicts that the use of a negative Poisson’s ratio structures in linear actuator systems would lead to optimized work in a high-stroke, low-force configuration . Several studies have shown that materials with a negative Poisson’s ratio can exhibit shape memory behavior, which could be used for building thermally activated medical stents and soft actuators. ,, A honeycomb structure has been as well used for DEA preparation, where the use of this structure gives additional prestretching of the DE membrane and allows a high anisotropy that leads to uniaxial actuations . The concept of folding and unfolding of cells using a pneumatic actuation has been described as well by Overvelde et al A prepared actuator showed a high degree of freedom, being able to actuate in various dimensions and being able to be folded flat .…”
Section: Mechanisms Of Shape Transformation and Locomotionmentioning
confidence: 99%
“…162,447,448 A honeycomb structure has been as well used for DEA preparation, where the use of this structure gives additional prestretching of the DE membrane and allows a high anisotropy that leads to uniaxial actuations. 449 The concept of folding and unfolding of cells using a pneumatic actuation has been described as well by Overvelde et al A prepared actuator showed a high degree of freedom, being able to actuate in various dimensions and being able to be folded flat. 450 Materials having a negative Poisson's ratio are interesting not only due to their mechanical properties but as well for their ability to exhibit an actuation to various dimensions.…”
Section: Effect Of Structure On Shape Transformationmentioning
confidence: 99%
“…The resulting curled-up structures followed predictions using minimization of energy approach and showcased how three-dimensional complex actuators could be built using intelligent design of printed patterns onto a DE substrate. Similarly, honeycombs of TPU were patterned using FDM into both sides of acrylic DE substrates to obtain anisotropic unidirectional actuators [ 65 ]. Higher degrees of anisotropy were obtained by varying the rib angle of the honeycombs and increasing the pre-stretch ratios of the DEs during print.…”
Section: Methodsmentioning
confidence: 99%
“…The nematic elastomer bears the most abundant mechanical properties and has been studied extensively [ 3 , 4 , 5 , 6 , 7 ]. Recently, nematic elastomer has been widely used in the fields of micro/nano devices, sensors and actuators [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%